Upaya Meningkatkan Hasil Belajar Siswa Menggunakan Model LAPS Heuristik pada Mata Pelajaran Matematika Kelas IV SD IT AL Qonita Palangka Raya - Abdul Wahid; Sulistyowati Sulistyowati; Istiyati Mahmudah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
This study aims to: (1) describe the implementation of mathematics learning using the LAPS (Logan Avenue Problem Solving) Heuristic learning model. (2) Describe the improvement of student learning outcomes after using the LAPS (Logan Avenue Problem Solving) Heuristic learning model. This study used a Classroom Action Research (PTK) approach which was carried out in two cycles. Each cycle includes four stages, namely planning, implementation, observation, and reflection. The research subjects were fourth grade students of SD IT Al Qonita with a total of 21 students. Research data were collected through learning outcome tests, observations of student and teacher activities, and interviews with teachers. Data analysis was carried out descriptively quantitatively to determine changes in learning outcomes and increased student activity during learning. The results showed that (1) The implementation of mathematics learning with the Logan Avenue Problem Solving (LAPS) Heuristic model showed improvement. In cycle I, the teacher's activity in managing the class reached 86.6% (very good category), and increased to 90% in cycle II. Student activities also increased, from 82.8% in cycle I to 91% in cycle II, both in the very good category (2) The use of the LAPS (Logan Avenue Problem Solving) Heuristic learning model can improve student learning outcomes. The results of classical completeness in cycle I reached 57.1% while in cycle